Effect of the Structural and Morphological Properties of Surfactant-Assisted Hydroxyapatite on Dermal Irritation and Antibacterial Activity - Giovanni García Domínguez (MDPI AG, 2021)
Hydroxyapatite (HAp) nanoparticles with a homogeneous rod morphology were successfully synthesized using the hydrothermal method. The powders were characterized using Fourier transform infrared spectroscopy, X-ray diffraction, and scanning electron microscopy. The antibacterial and dermal irritation analyses of the samples were performed and discussed. The use of cationic and anionic surfactants, namely, cetyltrimethylammonium bromide (CTAB) and sodium dodecyl sulfate (SDS), respectively, at a low concentration (2.5 mol%) modified the length/diameter (L/D) ratio of the HAp rods. Structural characterizations of hydroxyapatite synthesized without surfactant (HA), with 2.5 and 5 mol% of SDS (SDS− and SDS+, respectively), and with 2.5 and 5 mol% of CTAB (CTAB− and CTAB+, respectively) revealed well-crystallized samples in the hexagonal phase. The CTAB− sample presented antibacterial activity against Pseudomonas aeruginosa, Escherichia coli, Streptococcus anginosus, Staphylococcus aureus, Micrococcus luteus, and Klebsiella pneumoniae, suggesting that antimicrobial susceptibility was promoted by the bacterial nature and the use of the surfactant. Dermal irritation showed no clinical signs of disease in rabbits during the study, where there was neither erythema nor necrosis at the inoculation sites.